Drug Target Identification Using Affinity Core‐Shell Magnetic Nanoparticles and Mass Spectrometry. Issue 6 (29th April 2013) - Wei, Yunhuan; Wang, Tongdan; Liu, Chao; Zhang, Qianqian; Wang, Lishun; Tang, Gongli; Kang, Jingwu
Abstract Affinity core‐shell magnetic nanoparticles (MNPs) were prepared for identifying the target proteins of drugs in the cell lysate when used in combination with nano‐high‐performance liquid chromatography tandem mass spectrometry (HPLC‐MS/MS)‐based shotgun proteomic analysis. A number of new potential targets of cyclosporine A (CsA) could be identified, owing to the high efficacy of the affinity MNPs in drug target identification. To the best of our knowledge, this is the first time to reveal such an abundant target spectrum of CsA.